Robotic surgery in Asia. (October 2021) - Khan, Safinaz; Ataullah, A.H.M.; Khan, Robert Ahmed; Al-Salihi, Mohammed Maan; Rahman, Sabrina; Rahman, Md Moshiur
Abstract : The percentage of robot-assisted radical cystectomy (RARC) is comparatively low in Asia compared to other continents [11 ]. Few studies showed, RARC with intracorporeal urinary diversion causes less bleeding and hospital stay compared with extracorporeal urinary diversion.